'Full fusion' is not ineluctable during vesicular exocytosis of neurotransmitters by endocrine cells. (January 2017) - Oleinick, Alexander; Svir, Irina; Amatore, Christian
Abstract : Vesicular exocytosis is an essential and ubiquitous process in neurons and endocrine cells by which neurotransmitters are released in synaptic clefts or extracellular fluids. It involves the fusion of a vesicle loaded with chemical messengers with the cell membrane through a nanometric fusion pore. In endocrine cells, unless it closes after some flickering ('Kiss-and-Run' events), this initial pore is supposed to expand exponentially, leading to a full integration of the vesicle membrane into the cell membrane—a stage called 'full fusion'. We report here a compact analytical formulation that allows precise measurements of the fusion pore expansion extent and rate to be extracted from individual amperometric spike time courses. These data definitively establish that, during release of catecholamines, fusion pores enlarge at most to approximately one-fifth of the radius of their parent vesicle, hence ruling out the ineluctability of 'full fusion'.